Analisis Pengendalian Puncak Banjir Menggunakan Kolam Retensi di DAS Batang Air Dingin Kota Padang - Fajri Ramadhan -; Yola Amelia -; Revalin Herdianto -; Elvi Roza Syofyan (Jurnal Ilmiah Poli Rekayasa, 2020)
Batang Air Dingin Watershed is one of the watersheds in Padang City which is located at 00050’12,5” to 00050’22,5” South Latitude and 100023’35,85” to 100022’42,84” East Longitude has changed its function. Land in the area around the river flow results in greater surface runoff, which has the potential to cause erosion. Runoff that occurs in Batang Air Dingin Watershed area causes the river to shrink during the dry season causing the local residents’ wells to be drought, while in the rainy season the river discharge value used is obtained. Through the calculation of the hydrograps discharge using the HSS Nakayasu and HEC-HMS methods whose values are validated by the field flood discharge. Hydraulic modelling using HEC-RAS software with discharge from HSS Nakayasu method. The retention pond plan is based on the amount of runoff that cannot be accommodated by the original storage capacity of Batang Air Dingin Watershed during 100 year return period was 1212, 94 m3/second with large river storage capacity is 1205,317 m3/second. The debit that can be deducted by making a retention pond is 30,5%.